STRATEGIES IN IMPROVING STUDENTS' CREATIVE THINKING SKILLS AND GEOGRAPHICAL LEARNING OUTCOMES IN 21ST CENTURY - Miyatun Miyatun; Chatarina Muryani; Puguh Karyanto (GeoEco, 2021)
The development of the 21st century is marked by the use of advances in information and communication technology. Its application in the field of education requires students to be able to fulfill various skills. Creative thinking skills are important in the learning process because it is one of the higher-order thinking skills needed to face future challenges. This research was conducted to test the effectiveness of improving creative thinking skills and testing the effectiveness of improving student learning outcomes in social studies learning material on the physical condition of the Indonesian region at Junior High School. The method used in this research is Classroom Action Research (CAR) through cycle stages. This method is used to find out the best practices to achieve the learning objectives. The subjects of this study were 20 students of class VII Junior High School. Data analysis used the calculation of the creative thinking observation scale followed by an analysis of the percentage of students’ complete learning outcomes. The results show that students’ creative thinking skills increased to a very high category in cycle III. Analysis of the percentage of mastery learning outcomes reaching 90% with the average student score of 74,8 in cycle III.